An Exploratory Study of Possible Correlates of Individual Whistleblowing Propensity Among Sworn Staff in a City Jail - Wells, James B. (Criminal justice policy review, 2021)
Staff are essential to running safe and humane correctional institutions. To this end, staff sometimes need to report coworker misconduct. Doing so requires a propensity to engage in whistleblowing, a topic that has received very little attention in the criminal justice literature. Using results from the Work Experiences Questionnaire (WEQ), an instrument designed to measure various features of correctional work environments, we found several exploratory variables to be significantly associated with individual whistleblowing propensity. Specifically, male staff, White staff, and staff with college degrees had higher propensity scores. Increases in job satisfaction and organizational whistleblowing propensity were also related to greater willingness to report wrongdoing, whereas affective organizational commitment had a negative effect. To the extent replicated, such findings can guide policy and practice concerning the reporting of correctional staff wrongdoing.